Gambaran Praktik Komunikasi Terapeutik dan Komunikasi Sosial Perawat dalam Pemberian Pelayanan Keperawatan - Asrin; Kamaluddin, Ridlwan; Ekowati, Wahyu (Jurusan Keperawatan FIKES UNSOED, 2006)
Communication is a basic of a nursing care process. Communication is therefore very important because it could influence the level of patient satisfaction with health care services, increase of adaptation during hospitalisation, increase of adaptation for doing task that can cause a stress, decrease of pain, and accelarate of recovery. On the other hand, poor of communication is a main source of patient dissatisfaction. This research was conducted to know the description of nursing therapeutic communication and social communication practice by the nurses at Prof. Dr. Margono Soekarjo Hospital of Purwokerto. This study utilized a descriptive method with quantitative approach. The population of this study were all nurses at Prof. Dr. Margono Soekarja Hospital of Purwokerto. The respondents were nurses who did a communication with patients on medical and surgical wards at Prof. Dr. Margono Soekarjo Hospital of Purwokerto. The sampling method was done by quota sampling. The analysis of data was conducted by using the descriptive analysis. The study result shows that all techniques of nursing therapeutic communication were utilised by the nurses in caring the patients. The most often technique of therapeutic communication that is utilised by nurses are silent technique with frequency 150 (22,6%). While the technique of therapeutic communication that fewest utilized by nurses are reflection with frequency 12 (1,8%). Hereinafter, for the frequency of communication that can be seen according to shift work nurse can be concluded that morning shift show biggest communications frequency that is 243 times ( 36,4%) caught up with noon shift equal to 234 times (35%) , and at least for the shift of night equal to 191 times ( 28,6%). Other side, social communications which used by nurse in caring the patients consist of social discussion, family discussion, child concern discussion, vacation concern discussion, discussion concerning happiness/gladness and giving advise. Overall of social communications were most utilized by nurse in caring the patients are giving advise with amount 114 ( 37,9%). While the fewest social communications that used by nurse in caring the patients is personal discussion with amount 1 ( 0,3%). According to shift work nurse, the most social communications frequency that used is in the mornings shift that amount 111 ( 36,9 %) and the fewest is at noon shift counted 90 ( 29,9%). Conclusion of research can be descripted that all therapeutic communications technique were utilized by nurse in caring the patients and the most often technique of therapeutic communication that is utilised by nurses are silent technique and also which is the fewest technique that used by nurse is reflection technique. Pursuant to shift work nurse the most therapeutic communications done at morning shift. While for the technique of social communications which most is used is giving advise and also which is rarest used is personal discussion with biggest communications amount done at morning shift